2004
DOI: 10.1074/jbc.m402937200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt10b Inhibits Development of White and Brown Adipose Tissues

Abstract: Wnt is a family of secreted signaling proteins that regulate diverse developmental processes. Activation of canonical Wnt signaling by Wnt10b inhibits differentiation of preadipocytes in vitro. To determine whether Wnt signaling blocks adipogenesis in vivo, we created transgenic mice in which Wnt10b is expressed from the FABP4 promoter. Expression of Wnt10b in adipose impairs development of this tissue throughout the body, with a decline of ϳ50% in total body fat and a reduction of ϳ60% in weight of epididymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
299
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(322 citation statements)
references
References 39 publications
19
299
1
3
Order By: Relevance
“…Likewise, activation of the Wnt pathway in adipose tissue decreases fat mass in mammals (21,22,27). Together with our findings, this effect may suggest that a distortion in proper Wg signaling may interfere with normal fat body functions, having consequences on mosquito reproductive processes.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Likewise, activation of the Wnt pathway in adipose tissue decreases fat mass in mammals (21,22,27). Together with our findings, this effect may suggest that a distortion in proper Wg signaling may interfere with normal fat body functions, having consequences on mosquito reproductive processes.…”
Section: Discussionmentioning
confidence: 49%
“…Overexpression of Wg in the Drosophila fat body results in lethality at the pupal stage and a reduction of fat body mass in third-instar larvae, demonstrating the role of Wg signaling in the fat body for fat regulation (20). Likewise, activation of the Wnt pathway in adipose tissue decreases fat mass in mammals (21,22). Together with our findings, this effect may suggest that improper Wg signaling, such as the disruption of miR-8 expression, may interfere with normal fat body functions, including the synthesis and secretion of YPPs by the female mosquito fat body.…”
Section: Mir-8 Depletion Results In Impaired Ypp Secretion By the Fatmentioning
confidence: 99%
“…Transgenic mice expressing Wnt10b under the control of the adipose-specific fatty acid binding protein-4 (FABP4) promoter (FABP-Wnt10b) show a 50% decline in total body fat and are resistant to high-fat-diet-induced white adipose tissue accumulation [39]. In addition to reduced adiposity, FABP-Wnt10b mice exhibit an increase in bone mass [40].…”
Section: Discussionmentioning
confidence: 99%
“…46 Transgenic mice with adipose-tissue-specific overexpression of Wingless-type MMTV integration site family, member 10B (WNT10B) display a 50% reduction in body fat. 47 Christodoulides et al 48 have identified one proband with early onset obesity, who is heterozygous for a WNT10 C256Y mutation, which blocks adipogenesis. All relatives of the proband who carries this allele are either overweight or obese, whereas it has not been found in 600 control alleles.…”
Section: Adipogenesismentioning
confidence: 99%